Environmental Development of the External Genitalia - Maurizio, Ciro (East Carolina University, 2018)
Hypospadias is one of the most common birth defects in the world. The incidence of hypospadias has nearly doubled over the past 50 years and now occurs on average in 1 in 125 male newborns each year. Hypospadias is a malformation of the penis where the urethra does not exit at the distal tip, but rather ventrally along the shaft of the penis. The severity of hypospadias depends on the amount of preputial swelling closure, the urethral exit, and the overall shape of the penis. The presence of anti-androgenic and estrogenic endocrine disrupting chemicals (EDCs) in the environment is strongly linked with hypospadias incidence and severity. Still very little is known about the basic biology of penis development, how EDCs perturb normal development, and in-turn there are no known prenatal preventative treatments to protect the developing fetus from EDC exposure and abnormal penis development. In this dissertation I first review the basic biology of penis development. Then using geometric morphometrics I investigate the impact of the anti-androgen, vinclozolin, on morphological changes in the external genitalia. Based on where EDCs impacted penis development the most I then developed a quantitative scoring system to efficiently analyze variation in penis development. The scoring system then was implemented to investigate the temporal and endocrinological drivers of hypospadias severity. Lastly, I used the basic biological information gained to investigate a potential prenatal preventative to protect the developing fetus from EDCs.
Keywords: Endocrine Disruption; Hormone; Penis--Abnormalities; Hypospadias